2004
DOI: 10.1111/j.1462-5822.2004.00420.x
|View full text |Cite
|
Sign up to set email alerts
|

Candida albicans and Streptococcus salivarius modulate IL-6, IL-8, and TNF-alpha expression and secretion by engineered human oral mucosa cells

Abstract: SummaryWe investigated the involvement of oral epithelial cells via two cytokines (IL-6 and TNF-a a a a ) and one chemokine (IL-8) in local defences against live yeast (C andida albicans ) and bacteria ( Streptococcus salivarius ) using an engineered human oral mucosa model. We report that the yeast changed from the blastospore to the hyphal form and induced significant tissue disorganization at later contact periods (24 and 48 h) compared to the bacteria. However, this effect did not reduce the viability or t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
32
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 62 publications
8
32
0
3
Order By: Relevance
“…1). However, in previous studies, it has been observed that the secretion of such cytokines as IL-1, IL-1, IL-6, TNF-and/or GM-CSF in addition to IL-8 was enhanced in oral and vaginal epithelial cells and keratinocyte by C. albicans [40][41][42][43] and Malassezia spp. 43) It has also been reported that non-pathogenic and pathogenic bacteria such as probiotic Lactobacillus plantarum and L. johnsonii, 1-3) Bacillus subtilis (natto), 4) Salmonella dysenteriae, 5,6) enteroinvasive Escherichia coli 5,6) and Listeria monocytogenes 5) enhanced the secretion of various cytokines and eicosanoids in addition to IL-8 from IEC-like cells.…”
Section: Discussionmentioning
confidence: 92%
“…1). However, in previous studies, it has been observed that the secretion of such cytokines as IL-1, IL-1, IL-6, TNF-and/or GM-CSF in addition to IL-8 was enhanced in oral and vaginal epithelial cells and keratinocyte by C. albicans [40][41][42][43] and Malassezia spp. 43) It has also been reported that non-pathogenic and pathogenic bacteria such as probiotic Lactobacillus plantarum and L. johnsonii, 1-3) Bacillus subtilis (natto), 4) Salmonella dysenteriae, 5,6) enteroinvasive Escherichia coli 5,6) and Listeria monocytogenes 5) enhanced the secretion of various cytokines and eicosanoids in addition to IL-8 from IEC-like cells.…”
Section: Discussionmentioning
confidence: 92%
“…TLR2 and TLR4 are implicated in the recognition of various bacterial cell wall components, such as lipopolysaccharide (LPS), but TLR2 plays a major role in Gram-positive bacterial recognition. When combined with an agonist, TLR2 induces the activation of NF-κB via a MyD88-dependent/independent pathway and stimulates the production of many proinflammatory cytokines, such as TNF-α, IL-6, IL-12, IFN-α and IFN-γ (Zhang and Ghosh, 2001;Mostefaoui et al, 2004). We hypothesized that the response of the TLR signaling pathway to heat stress may play a role in stress-induced immune suppression.…”
Section: Discussionmentioning
confidence: 99%
“…Cytokines are known to play a critical role in protection against bacterial, fungal, and viral infections, and have been found to be involved in the pathogenesis and development of symptoms of infection [6]. Inflammatory responses are advantageous for eradicating bacteria, as long as they are under control, but when they are out of control, a massive production of pro-inflammatory cytokines (e.g., IL-6) can cause tissue injury and even multiple organ failure.…”
Section: Introductionmentioning
confidence: 99%